Kocip fatimah in RED BULL energy drink? - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Safriza, Baharuddin; Muhammad Najib, Muhammad Nor; Noor Azhar, Abd. Rasid (Penerbit UMP, 2009)
MAR 20 KUALA LUMPUR: Allswell Trading pte, Ltd. (Singapore) expressed interest to explore incorporating the research grade Kacip Fatimah extract as prepared by Prof Mashitah Mohd Yusoff in Red Bull Energy Drink.